Multiple Intervention in Single Setting: Report on Cases over One Year (Cardiovascular Journal, 2016)
Background: Association of various types of congenital lesions in a single patient is a very common finding in congenital heart disease cases. Many such lesions are amenable to nonsurgical interventions in single setting. Such interventions along with surgical intervention are also possible in hybrid laboratories. Here we are reporting on our experience of twelve cases of multiple interventions in the year 2015.Methods: This is a retrospective review of double or multiple interventions done on cases from January 2015 to December 2015 In Lab aid cardiac hospital and Combined Military Hospital Dhaka. Type of Congenital lesions were identified from chest x-ray, ECG, and colour Doppler Echocardiography and combination of interventions were planned accordingly.Results: Out of twelve cases, 66.66% were male and 33.34% were female. Majority of cases (50%) were in 4-8 years age group. Most common type of disease combination was Atrial Septal Defect (ASD) with Patient Ductus Arteriosus (PDA). Association of Ventricular Septal Defect (VSD) with PDA was found in 16.67% cases, combination of PDA with coarctation of aorta was found in 16.67% cases and combination of ASD and VSD was found in 16.67% cases. Combination of ASD, VSD, PDA was also found with aortic and pulmonary stenosis in some cases. Outcome of multiple interventions in all the cases were good.Conclusion: Existence of multiple simple congenital heart lesions is a commonly encountered problem in Pediatric cardiac Practice. Multiple Interventions can be done on these lesions safely. Multiple interventions can be done on complex cases also for life saving purpose. One years experience of multiple intervention reported in this study showed excellent outcome.Cardiovasc. j. 2016; 9(1): 36-42